MAb‐based competitive ELISA for the detection of antibodies against influenza D virus. Issue 1 (17th September 2018) - Moreno, Ana; Lelli, Davide; Lavazza, Antonio; Sozzi, Enrica; Zanni, Irene; Chiapponi, Chiara; Foni, Emanuela; Capucci, Lorenzo; Brocchi, Emiliana
Abstract: Influenza D virus (IDV) was first reported in 2011 in swine in Oklahoma and consequently found in cattle, sheep, and goats across North America and Eurasia. Cattle have been proposed as the natural reservoir. In this study, we developed and validated a MAb‐based competitive ELISA for the detection of antibodies against IDV. Thirty‐one hybridomas specific to IDV were generated using Balb/C mice immunised with purified IDV/Swine/Italy/199724‐3/2015. The specificity of MAbs was determined by comparing their reactivity with the homologous and other influenza A viruses along with additional bovine and swine viruses. A solid‐phase competitive ELISA (IDV‐cELISA) was set up using the partially purified antigen coated to the plate and incubation of two serum dilutions (1/10 and 1/20) followed by addition of a peroxidase‐conjugated MAb as competitor, which had shown wide intratype cross‐reactivity and positivity in HI. To evaluate the diagnostic performances of IDV‐cELISA, we used 884 sera (414 negative and 470 positive) from different species. ROC analyses were performed to enable the selection of best cut‐off value and estimation of diagnostic specificity and sensitivity. The agreement between IDV‐cELISA and HI test was assessed by Cohen's kappa value (κ). The κ analysis showed an almost perfect agreement (κ = 0.93; 95%CI −0.899 to 0.961) between HI test and IDV‐cELISA. ROC analysis showed that IDV‐cELISA was accurate with an area under the curve (AUC) = 0.999, 95% CI 0.993–1.000). A cut‐off value of 65% was selected with Se and Sp values of 99.35 (95% CI 98.1–99.9) and 98.75 (95% CI 97.1–99.6). These results proved excellent diagnostic performances of IDV‐cELISA, which compared to HI presented major advantages, such as suitability for automation, low dependence on individual skills, spectrophotometric reading, and easy interpretation of the results. This assay can be exploited to detect anti‐IDV antibodies in different animal species.